Popularity of marijuana among Polish students - Michał Pająk (Journal of Education, Health and Sport, 2017)
Introduction and the aim: Marijuana is the most commonly used drug in the world (excluding alcohol and tobacco). According to the literature about 16% of Poles at the age of 16 to 64 years old, at least once have used cannabis. The aim of study was to estimate the popularity of marijuana among students of Polish universities. We also asked questions about respondents’ attitude towards marijuana and opinions about its validation.